Analysis of the Effect of ChatGPT on The Learning Productivity of Secondary School Students - Salmaan, Axel Faiz (Proceeding International Conference on Education, 2023)
This study directs readers to find out the effect of chatGPT on the learning productivity of high school students. In the industrial era 5.0, humans have fast-paced demands in carrying out various activities in daily life. This study used a simple regression analysis technique to determine the significant difference between chatGPT and student productivity in secondary schools. Data collection was carried out using a questionnaire and given to 25 students of MTsN 2 Kota Kediri. The data that has been collected will be analyzed using simple regression consisting of several tests including, normality and linearity tests, and heteroscedasticity tests. From these tests, the results obtained a significance value above 0.05 so it can be concluded that the use of chatGPT affects student learning productivity